2023
DOI: 10.25122/jml-2023-0178
|View full text |Cite
|
Sign up to set email alerts
|

Assessing pyridoxine adjuvant therapy effects on blood glucose levels in type 2 diabetes: A randomized clinical trial

Moatamad Hanoon Dawood,
Manal Khalid Abdulridha,
Hayder Saadoon Qasim

Abstract: is the bioactive derivative of vitamin B6, functioning as a coenzyme in over 150 metabolic pathways. Insufficient PLP levels could be associated with the onset and progression of diabetes. This study aimed to assess the effects of pyridoxine adjuvant treatment on blood glucose levels in patients with type 2 diabetes mellitus (T2DM). This interventional, randomized, open-label study was conducted in the Mesan Governorate, with participants from the Mesan Center for Diabetes and Endocrinology as the study popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…For example, RCT with the participation of women with excess weight undergoing an 8-week weight reduction program (see Table 5) showed that such supplementation had a significant, positive effect on FI and HOMA-IR compared to the control group receiving a placebo [77]. In addition, other studies demonstrated lower postprandial glucose levels in healthy adults when vitamin B6 was administered 20 min before the oral glucose tolerance test (OGTT) [129] and a decrease of FG, FI, HOMA-IR, and HbA1c in T2D patients undergoing a 4-week supplementation [130]. In the la er study, the authors used vitamin B6 supplementation at a high dose of 300 mg/day compared to 80 mg/day and 50 mg/single dose in the former two studies.…”
Section: Effects Of Micronutrient Supplementation On Glucose Homeostasismentioning
confidence: 99%
“…For example, RCT with the participation of women with excess weight undergoing an 8-week weight reduction program (see Table 5) showed that such supplementation had a significant, positive effect on FI and HOMA-IR compared to the control group receiving a placebo [77]. In addition, other studies demonstrated lower postprandial glucose levels in healthy adults when vitamin B6 was administered 20 min before the oral glucose tolerance test (OGTT) [129] and a decrease of FG, FI, HOMA-IR, and HbA1c in T2D patients undergoing a 4-week supplementation [130]. In the la er study, the authors used vitamin B6 supplementation at a high dose of 300 mg/day compared to 80 mg/day and 50 mg/single dose in the former two studies.…”
Section: Effects Of Micronutrient Supplementation On Glucose Homeostasismentioning
confidence: 99%